SOCIAL STATUS OF WOMEN IN THE SOCIETY: AN ABERRATION FROM THE CONSTITUTIONAL DECLARATION(S) OF EQUALITY OF MEN AND WOMEN - Ngozi, Nwosu P. (Sokoto Educational Review, 2020)
The paper examines the social status of the female in the Nigerian society. In doing this, the author mentions the secondary position occupied by women in ancient societies to the present day. The caustic experience of women in terms of the differential training given to the girl-child, the differences in inheritance practice in many societies, the overriding power of men over women, the discriminatory burdens placed on women, and the role played by male writers have made women to seemingly accept the status given to them by men dominated society. All the constitutions of the world give inalienable rights to women. The writer therefore conclude that women should see themselves as capable of changing themselves and the world they live in irrespective of the constitutional aberration.